Sensitivity profile of carbapenem-resistant uropathogenic bacterial isolates to Cefiderocol - Fatemeh Omidi; Leila Fozouni; Arash Nikyar; Mehr Ali Mahmood Janlou (Jorjani Biomedicine Journal)
Background: Cefiderocol is a siderophore cephalosporin with unique cell-penetrating abilities against multidrug-resistant (MDR) Gram-negative bacteria, especially carbapenem-resistant strains. This study aimed to evaluate the prevalence and susceptibility profiles of Cefiderocol on carbapenem-resistant uropathogenic Escherichia coli and Klebsiella pneumoniae isolates among hospitalized patients. Methods: One hundred twenty-nine patients more than 72 h admitted to hospitals participated from Feb. 2021 to Dec. 2022. Urine samples were examined to identify uropathogenic K. pneumoniae and E. coli isolates based on microscopic morphology, cultural and biochemical methods. The carbapenemase production in the isolates was evaluated using modified Hodge tests and PCR. The MIC of Cefiderocol against carbapenemase-producing isolates was evaluated according to CLSI-2021 guidelines. Results: According to phenotypic and genotypic tests, among forty-two E. coli isolates (71.19%) were carbapenemase positive, 38 isolates had the blaOXA gene (90.47%), and among twenty-four K. pneumoniae isolates 96% contained the blaKPC gene. In MIC determination 55.24% of carbapenem-resistant E. coli isolates were inhibited with ≤0.5 μg/ml of Cefiderocol, while only two strains (8.33%) of K. pneumoniae isolates showed resistance to the Cefiderocol (MIC90=2 μg/ml). Conclusion: The present results demonstrate that the emergence of carbapenem-resistant uropathogenic bacteria poses a critical health threat to society. Based on the results, Cefiderocol demonstrated efficacy against carbapenem-resistant clinical isolates at low concentrations.